Phytochemicals as Substances that Affect Astrogliosis and their Implications for the Management of Neurodegenerative Diseases - Forouzanfar, Fatemeh; Pourbagher-Shahri, Ali M.; Vafaee, Farzaneh; Sathyapalan, Thozhukat; Sahebkar, Amirhossein (Current Medicinal Chemistry, 2024)
Astrocytes are a multifunctional subset of glial cells that are important in maintaining the health and function of the central nervous system (CNS). Reactive astrocytes may release inflammatory mediators, chemokines, and cytokines, as well as neurotrophic factors. There may be neuroprotective (e.g., cytokines, like IL-6 and TGF-b) and neurotoxic effects (e.g., IL-1β and TNF-a) associated with these molecules. In response to CNS pathologies, astrocytes go to a state called astrogliosis which produces diverse and heterogenic functions specific to the pathology. Astrogliosis has been linked to the progression of many neurodegenerative disorders. Phytochemicals are a large group of compounds derived from natural herbs with health benefits. This review will summarize how several phytochemicals affect neurodegenerative diseases (e.g., Alzheimer's disease, Huntington's disease, amyotrophic lateral sclerosis, and Parkinson's disease) in basic medical and clinical studies and how they might affect astrogliosis in the process.
Keywords: Astrocytes